Effects of sublimation temperature on cell microstructure of pear melon during vacuum freeze drying - TIAN Jinjin; YAO Chaoyang; ZHANG Zhiqiang; ZHANG Zhe; JI Hongwei; WU Jinyu (Shipin yu jixie)
Objective: This study aimed to obtain optimal sublimation temperature of pear melon cells. Methods: The pre-freezing cooling rate and vacuum pressure were selected by optimization method to be 25 ℃/min and 10 Pa, respectively, based on cryogenic microscope imaging and vacuum freeze-drying technology. Then, sublimation temperatures of 10, 5, 0, -4, -7 and -10 ℃ were used for experimental research. The morphological parameters (equivalent diameter, area, circumference, volume), internal pressure, and porosity of cells during the process of dehydration and drying were analyzed. Results: As the sublimation temperature rose, the morphological parameters of different dimensions of cells first decreased and subsequently increased. The change rates of equivalent diameter, cross-sectional area, and volume of cells were 5.05%, 9.60%, and 14.68% after drying at 0 ℃, which well preserved the original morphological structure of cells. At the same time, with the increase of dimension, the change amount at the same sublimation temperature also increases. Conclusion: Combined with the optimal pre-freezing rate and vacuum degree, the optimum temperature condition of pear melon drying sublimation is 0 ℃.